Apple snails as vectors of trematodes: molecular identification of the larval stages that parasites the digestive gland of some argentinian ampullariids - Dellagnola, F. A. (2020)
In the context of a broader program dealing with the symbiotic associations of apple snails, wesampled some species of Neotropical ampullariids that occurs mainly in the Paraná-Uruguayriver basins (Argentina). Different larval stages (sporocysts, rediae, and cercariae) of flukes arefound in the digestive gland of these freshwater snails. Asolene platae showed trematode larvae(echinocercariae and xiphidiocercariae) in haemocoelic spaces and connective tissue of thedigestive gland. The echinocercaria resembled those of the genus Echinochasmus, but lackedsensory hairs on the body and tail whereas the xiphidiocercaria was similar to theXiphidiocercaria armatae belonging to the Opisthoglyphe type. Also, we described for the firsttime the cercarial stage of Stomylotrema vicarium in the host Pomacea americanista fromMisiones rain forest, which showed a big stylet in the oral sucker and three pairs of penetrationglands. Moreover, a molecular multilocus approach (using the 28S rRNA, ITS1 and mtCOXIsequences) was used to infer the phylogenetic position and understand their life cycle. The 28SrRNA gene linked the echinocercarial sequences with the polyphyletic genus Echinochasmus,while the xiphidiocercarial sequences were linked with the genus Phaneropsolus. Sequences ofthe trematode larval stages from P. americanista were grouped (genetic distance ranged 0.02%and 0.05%) with two sequences from adult Stomylotrema vicarium. Both ITS1 y mtCOXIsequences confirmed the phylogenetic position of the larvae inside of Echinochasmidae,Phaneropsolidae, and Stomylotrematidae. Finally, the three molecular markers were useful todistinguish cryptic molecular entities from a single echinocercarial morphotype, morphologicallyundistinguished, in the host A. platae.